Low-temperature torrefaction of organic waste as a fuel source for pulverized coal boilers. Part I - Karcz, Henryk; Grabowicz , Michał (Instal, 2019)
Rational management of natural fuels is a basic condition for the functioning of the entire economy, especially in Poland, where raw material resources are limited in many areas. Due to the fact that all products generated during combustion should be managed in accordance with applicable standards, scientific and application research in the field of processing all types of waste, constitute an area of innovation for the energy sector. The proposed solution goes towards the definition of such technological and material indicators that limit the amount of harmful substances emitted into the atmosphere that are created during thermal processing. Low-temperature carbonization of waste and biomass is one of the methods for preparing these substances for high-temperature use in the process of thermal valorisation. Torrefaction is a low-temperature way of preparing waste for use in the thermal utilization process in power boilers.